SCIENCE PREDICTION ON THE HADITH ABOUT THE SUN RISING FROM THE WEST - Zain, Muhammad Fajri Kholili; Hasan Fadly, Ahmad Mufarih (Fakultas Syari'ah dan Hukum UIN Walisongo, 2024)
There are a lot of holy texts in Islam, like Al-Qur'an and Hadith, discussing the Sun that will rise in the West. However, a study has yet to be conducted to explain this phenomenon from a scientific point of view. It creates several issues, such as the explanation of the Sun rising from the West from the point of view of religion and scientific terms, nor the way to prove and predict the time of this phenomenon. This research was compiled using a qualitative analysis method with a case study approach. This approach limits its analysis tools to one specific case. This study used an analysis of the Sun's azimuth shift at the time of the Equinox to prove the possibility of sunrise from the West. With this method, it is discovered that in a religious view, the rising Sun from the West is seen as a real event and will occur physically. Meanwhile, science is to explain how possible scenarios can cause this phenomenon to occur. In addition, an analysis of the shift in the Sun's rising point concerning the azimuth of the Sun at the time of Equinox cannot prove and cannot predict when the Sun will rise from the West, which is a sign of doomsday.